Computer-Generated Accounting Assignments. - Zieha, Eugene L. (The Accounting Review, 1974)
Abstract This article describes an educational innovation, computer-generated accounting assignments being developed and reduced to practice at the University of Missouri-Columbia. This instructional aid provides each student in a class with an individual, unique homework assignment on a given topic. Furthermore, it provides the student with the solution to his personal assignment. The traditional teaching aid of accounting, problems-oriented homework assignments, is substantially enhanced. The temptation to copy, inherent in the use of the identical problem for many students for several semesters, is eliminated.